Improving the Self-Healing of Cementitious Materials with a Hydrogel System - Hao Wang; Mohammad Habibi; Riadh Marzouki; Ali Majdi; Morteza Shariati; Nebojsa Denic; Aleksandar Zakić; Majid Khorami; Mohamed Amine Khadimallah; Ahmed Abdel Khalek Ebid (Gels, 2022)
Despite cement’s superior performance and inexpensive cost compared to other industrial materials, crack development remains a persistent problem in concrete. Given the comparatively low tensile strength, when cracks emerge, a pathway is created for gas and water to enter the cementitious matrix, resulting in steel reinforcement corrosion which compromises the durability of concrete. Superabsorbent hydrogels have been developed as a novel material for enhancing the characteristics of cementitious materials in which they have been demonstrated to decrease autogenous shrinkage and encourage self-healing. This study will detail the design and application of polyelectrolyte hydrogel particles as internal curing agents in concrete and provide new findings on relevant hydrogel–ion interactions. When hydrogel particles are mixed into concrete, they generate their stored water to fuel the curing reaction that results in less cracking and shrinkage, thereby prolonging the service life of the concrete. The interaction of hydrogels with cementitious materials is addressed in this study; the effect of hydrogels on the characteristics and self-healing of cementitious materials was also studied. Incorporating hydrogel particles into cement decreased mixture shrinkage while increasing the production of particular inorganic phases within the vacuum region formerly supplied by the swollen particle. In addition, considering the control paste, cement pastes containing hydrogels exhibited less autogenous shrinkage. The influence of hydrogels on autogenous shrinkage was found to be chemically dependent; the hydrogel with a delayed desorption rate displayed significantly low shrinkage in cement paste.